CORRELATION BETWEEN PERSONAL HYGIENE WITH CHROMIUM (Cr) AND ALBUMIN LEVEL IN URINE OF METAL COATING WORKERS IN SIDOARJO EAST JAVA INDONESIA - Nugroho, Mohammad Apriyan; Ningrum, R. Azizah, Nurul Fauziah; Ocvian, Brevy Nella Herny; Eriani, Izmi Dwira (International Journal of Psychosocial Rehabilitation, 2020)
Background: Metal coating process involves several chemicals one of them is chromium. Chromium plating workers have a high risk of chromium exposure. The effects of chromium on health cause carcinogenicity, immunodeficiency, nervous system disorders, kidney disease, and respiratory effects. Purpose of the research: To analyzed the correlation between personal hygiene and heavy metal chromium (Cr) levels in urine of metal coating home industry workers in Candi District Sidoarjo. Research Methods: This research used observational descriptive research with cross sectional design. The sample number of metal coating workers was 15 people. Chromium levels in the urine of workers were analyzed with Atomic Absorption Spectrophotometer (AAS). Urine Albumin levels were analyzed by Immunoturbidimetric Assay method. Personal hygiene behavior information was collected from questionnaire sheets. Analysis of descriptive data analysis used coefficient contingency to determine the strength correlation between variables. Research Results: 47% of respondents washed hands before working which embraced in poor category, with a positive albumin level of 43%. The 27% of respondents washed hands after working which embraced in poor category, with 75% above normal in urine chromium level and 25% positive albumin level. The 47% of respondents washed clothes after working which embraced in poor category, with 43% urine chrome level and 57% positive albumin level. The 42% of respondents washed shoes after working which embraced in poor category, with 60% above urine chrome level and 20% positive albumin level. The 20% of respondents in water consumption embraced in poor category, with 30% above normal in urine chromium level and 33% positive albumin level. The strongest correlation between personal hygiene and urine chromium levels in variable of hand washing before working, the Coefficient Contingency is 0.421 (moderate correlation), while personal hygiene and urine albumin levels in variable of washing clothes after working, the Coefficient Contingency is 0.471 (moderate correlation). Conclusion: Most of workers do not apply personal hygiene properly. The sub-variable that has the strongest correlation is the washing clothes habit before working and washing clothes after working. Thus, it is needed to apply good personal hygiene to workers. The home industry owner and the local government should carry out regular monitoring in controlling of waste produced, so it will not affect the workers.